Penyusunan Standar Operasional Prosedur (SOP) Produksi Katekin dan Tanin dari Gambir - Wedy Nasrul; Rudi Kurniawan Arief; Afdhil Arel (LPPM UMRI, 2024)
Standard Operating Procedures (SOP) for production are documents that contain step-by-step instructions to guide workers on how to carry out repetitive production processes for a job to achieve production goals. Production SOP function to guide workers in the production process and maintain the quality of the products produced. The Sharia Producer Cooperative